Penyuluhan Kesehatan Peduli Remaja Terhadap Pengetahuan Dan Sikap Remaja Tentang Seks Pranikah (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: World Health Organization (WHO) in 2010 to 210 million each year for pregnant teenagers aroundthe world, 46 million of them have an abortion because of the sex before marriage. One of the causes of pregnancyoutside of marriage is the inability of a teenager in a biological impulse control. From the data of the Ministry of Religious Bantul increasing cases of early marriage, and 95% of early marriage are caused by premarital pregnancy.Objective: To identify the level of knowledge and attitudes of teenagers in the village Girirejo premarital sex beforeand after counseling.Methods: This study used a quasi-experimental (quasi experiment) with the approach of one group pretest-posttestwith a till sample with purposive sampling method 56 adolescent youth village Girirejo, Imogiri and analyzed datawas analyzed by paired sample t-test with SPSS for windows 17.0 statistical test decision to use a significant levelof p